Modernism and still life : artists, writers, dancers - Tobin, Claudia (Edinburgh critical studies in modernist culture., 2020)
The late nineteenth and early twentieth centuries have been characterised as the 'age of speed' but they also witnessed a reanimation of still life across different art forms. This book takes an original approach to still life in modern literature and the visual arts by examining the potential for movement and transformation in the idea of stillness and the ordinary. It ranges widely in its material, taking Cézanne and literary responses to his still life painting as its point of departure. It investigates constellations of writers, visual artists and dancers including D.H. Lawrence, Virginia Woolf, David Jones, Winifred Nicholson, Wallace Stevens, and lesser-known figures including Charles Mauron and Margaret Morris. Claudia Tobin reveals that at the heart of modern art were forms of stillness that were intimately bound up with movement: the still life emerges charged with animation, vibration and rhythm; an unstable medium, unexpectedly vital and well suited to the expression of modern concerns.